ANALISIS DISKRIMINASI PENYANDANG DISABILITAS PADA PROSES REKRUTMEN (Studi Kasus Pada PT Grab) - Harmen, Hilma; yahreza, Dina Sarah; Umaira, Nabila; Ramadhani, Aulia; Fiqri, Muhammad Ilham; Lingga, Desmila Atheja Syahfitr; Zuhra, Naila; Hakim, Arif Rahman (Growth, 2024)
We hope to learn more about the impact of physical conditions on discrimination in the recruitment process at PT Grab using a qualitative research approach. Qualitative research method is employed to gain a deep understanding of individuals’ experiences with physical conditions in the recruitment process. This includes data coding, theme identification, and analysis of documents related to recruitment procedures at PT Grab, such as company diversity and inclusion policies. This research aims to identify factors influencing discrimination and measure its impact on job opportunities for individuals with physical limitations. Thus, It is anticipated to offer beneficial understandings for recruitment practitioners and human resource management in developing more inclusive recruitment policies. Through insight into the difficulties encountered by individuals with physical limitations, it is hoped that companies can implement more inclusive recruitment policies and create a more welcoming work environment for all individuals. This studies are anticipated to significantly advance the field of literature on employment inclusion and inspire other companies to adopt more inclusive recruitment practices and reduce discrimination in the workplace.